Breaking down barriers: Understanding the experience of British Pakistani families affected by imprisonment. (September 2016) - Abass, Tahir; Reeves, Carla; Raikes, Ben
This paper explores the experiences and support needs of British Pakistani families of prisoners through in-depth interviews with six family members of different prisoners: four males and two females, ranging between 18 and 40 years. Key findings are that British Pakistani family members of prisoners experienced the Criminal Justice System as culturally inappropriate and insensitive, raising questions of direct, indirect and institutional racism. Furthermore, family members were more likely to access support if criminal justice and support services staff were drawn from the wider British Pakistani community, but felt hindered from doing so if those staff were thought to have personal relationships to the families' own local communities.